Exergetic diagnostics of a gas-and-steam power plant = Diagnostyka egzergetyczna elektrowni gazowo-parowej - Stanek, Wojciech; Simla, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Evaluation of thermodynamic efficiency of a power plant is usually performed using the method of so-called thermal diagnostics, based on energy balancing. Energetic analysis is however suitable only for a quantitative assessment and for comparing similar technologies. In order to properly assess the origins of energy losses in the given system, an exergetic analysis has to be applied.
Keywords: combined cycle power plant; exergetic analysis; mathematical model; elektrownia gazowo-parowa; diagnostyka egzergetyczna; model matematyczny